The Role Of Islamic Financial Institutions Of BSI Bank In Empowering MSMEs Through The Sharia Micro Loan Program - Ali, Muhammad Rofikul; Rhomadhani, Haikal Nuril; Hidayatullah, D.w Fatikh (Universitas Mercu Buana, 2024)
This article is prepared with an effort focused on analyzing how BSI Bank Islamic financial institutions empower MSMEs through the sharia KUR acceptance program. The process of collecting data and information for writing this article adapts qualitative research methods through literature study techniques using books, articles, and scientific papers that are accessed electronically. Some of these data and information sources are accessed because they contain discussions that are in accordance with the topic. The data is then reduced to be classified and concluded in accordance with the subject matter of discussion contained in this article. The results of the discussion regarding the acceptance of the sharia KUR program on the empowerment of MSMEs. That the sharia KUR program can run smoothly and effectively. In accordance with several aspects stipulated in the sharia KUR program. The development of the sharia KUR program can increase sustainable growth and development for MSME business actors. The provision of capital as a matter that greatly affects the sustainability of the MSME business is also very effective. The sharia KUR program is beneficial for the growth and improvement of MSMEs; in addition to that, Yakini can also minimize the unemployment rate and expand new business fields or start new businesses.